The Role of Plasma Cells as a Marker of Chronic Endometritis: A Systematic Review and Meta-Analysis - Angela Santoro; Antonio Travaglino; Frediano Inzani; Giuseppe Angelico; Antonio Raffone; Giuseppe Maria Maruotti; Patrizia Straccia; Damiano Arciuolo; Federica Castri; Nicoletta D’Alessandris; Giulia Scaglione; Michele Valente; et al. (Biomedicines, 2023)
Chronic endometritis (CE) is the persistent inflammation of the endometrial lining associated with infertility and various forms of reproductive failures. The diagnosis of CE is based on the histological evidence of stromal plasma cells; however, standardized methods to assess plasma cells are still lacking. In the present paper, we aimed to determine the most appropriate plasma cell threshold to diagnose CE based on pregnancy outcomes. Three electronic databases were searched from their inception to February 2022 for all studies comparing pregnancy outcomes between patients with CE and patients without CE. The relative risk (RR) of pregnancy, miscarriage, and/or live birth rates were calculated and pooled based on the plasma cell threshold adopted. A p-value < 0.05 was considered significant. Nine studies adopting different thresholds (1 to 50 plasma cells/10 HPF) were included. In the meta-analysis, we only found a significant association between miscarriage rate and a plasma cell count ≥ 5/10 HPF (RR = 2.4; p = 0.007). Among studies not suitable for meta-analysis, CE showed an association with worsened pregnancy only when high thresholds (10 and 50/10 HPF) were adopted. In conclusion, our study suggests that the presence of plasma cells at low levels (<5/10 HPF) may not predict worsened pregnancy outcomes. Based on these findings, a threshold of ≥5 plasma cells/10 HPF may be more appropriate to diagnose CE.